ANALISIS PENGARUH BAURAN PRODUK TERHADAP MOTIVASI KUNJUNGAN WISATAWAN (STUDI KASUS MUSEUM TEKSTIL, JAKARTA) - Rustini Rustini (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
There were few studies concerning product mix. The research object of this study was Museum Textile Jakarta, where researcher was enthusiastic to observe the influence of product mix towards motivation of tourists visit. The research showed the researcher desire as well to museum tourism which Indonesian did not interest much to visit them, it was contrary with European for instance. Hopefully, this research was able to enhance Indonesian motivation to love more museum world thus coming to visit them eventually. The research reviewed 5 product mix variables (X), i.e., Type, Quality, Packaging, Positioning and Service and 2 motivation variables (Y), i.e., push factors and pull factors. From Stepwise method, result obtained was the most influence variable of X variable towards Y variable was Packaging.